Behavioral Changes in Dogs With Idiopathic Epilepsy Compared to Other Medical Populations - Levitin, Hilary; Hague, Devon Wallis; Ballantyne, Kelly C.; Selmic, Laura E. (Frontiers in Veterinary Science, 2019)
Anxiety related behaviors have been reported in humans diagnosed with idiopathic epilepsy (IE) and such traits may be altered depending on seizure phase. The purpose of this study was to determine the presence and severity of anxiety related behaviors in dogs with IE compared to other medical populations, and to determine if behavioral changes were associated with seizure control. In this retrospective cross-sectional study, the owners of one hundred and two dogs presenting for wellness examination (37), epilepsy (38), and intervertebral disc disease (27) were surveyed utilizing a questionnaire developed based on the shortened Canine Behavioral Assessment and Research Questionnaire (mini-CBARQ), previously validated for its ability to analyze canine behavior. Veterinarians of participating dogs completed a questionnaire to verify diagnoses. Dogs with IE and IVDD had a higher likelihood of being fearful/anxious when approached by an unfamiliar dog compared to the wellness group. Dogs with IE receiving polytherapy had decreased excitement before a walk (P= 0.0007) or car trip (P= 0.027), increased fear/anxiety when groomed (P= 0.0197), and increased shaking, shivering, or trembling when left alone (P= 0.0004) compared to dogs receiving monotherapy. Polytherapy dogs had increased agitation when their owner/others showed affection towards other people/dogs during preictal (Pperson= 0.005, Panimal= 0.0083), postictal (Pperson= 0.001, Panimal= 0.0068) and interictal (Pperson= 0.0083, Panimal= 0.02) period compared to monotherapy dogs. Seizure frequency and severity was not correlated with anxiety related behavior in dogs with IE. While seizure phase was associated with behavior changes in 38% (14/37) of our epileptic population, one specific seizure phase was not more likely to produce behavior changes than another. Behavioral changes noted in dogs with IE raises further questions about how this disease affects QoL.